1996
DOI: 10.1046/j.1365-277x.1996.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Food choice in response to computer‐generated nutrition information provided about meal selections in workplace restaurants

Abstract: Aim:The study was designed to determine the effect of computerized nutrition information on consumer food choice in two workplace restaurants, one in which customers had to pay for their lunch and the other providing a free lunch.Methods: Customers entering the restaurants were asked to make selections from the menu on a computer screen. The energy, saturated fatty acids, non-milk extrinsic sugars and non-starch polysaccharide content of the meal selected was displayed graphically in proportion to the dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The best approach for menu-based nutrition information, particularly for those consumers who may be limited in their food and health literacy skills, merits further exploration. No control or comparison group (preepost design) 17 [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Published before 1990 6 [83][84][85][86][87][88] Outcomes of interest (calories consumed, calories selected, and frequency of purchase of targeted items) were not measured…”
Section: Discussionmentioning
confidence: 99%
“…The best approach for menu-based nutrition information, particularly for those consumers who may be limited in their food and health literacy skills, merits further exploration. No control or comparison group (preepost design) 17 [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Published before 1990 6 [83][84][85][86][87][88] Outcomes of interest (calories consumed, calories selected, and frequency of purchase of targeted items) were not measured…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies 6,7 of menu labeling regulations consistently demonstrate increased customer awareness and use of calorie information. Evidence from most survey and experimental studies [8][9][10][11][12][13][14][15] suggests that provision of nutrition information on menus leads to healthier purchases. Realworld evaluations of restaurant menu labeling regulations soon after implementation have yielded mixed results regarding the impact on calories purchased, but these studies 6,7,[16][17][18][19] were conducted within 1 year after menu labeling was implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Even among studies finding an effect, the size of the effect tended to be small. For example, Balfour et al (1996) and Yamamoto et al (2005) found that only a small proportion of consumers (16% and 29%, respectively) changed their menu item selection when presented with nutrition information. Importantly, no previous studies have provided an estimate of the economic value of nutritional information on restaurant menus which could be used in a cost‐benefit analysis.…”
Section: Introductionmentioning
confidence: 99%